A balancing strategy for ambidextrous learning, dynamic capabilities, and business model design, the opposite moderating effects of environmental dynamism. (May 2021) - Yuan, Chun; Xue, Doudou; He, Xin
Abstract: The present study examines whether a balancing strategy for ambidextrous learning (BSAL) can influence business model design (BMD) via dynamic capabilities. Furthermore, this study investigates whether environmental dynamism, in an opposite manner, moderates the relationships between dynamic capabilities and novelty-centered and efficiency-centered BMD. It draws on a cross-industrial sample of 493 Chinese firms. Data are analyzed using a set of OLS regression models and the bootstrap procedure. Results show that dynamic capabilities mediate the positive effects of BSAL on novelty-centered and efficiency-centered BMD; environmental dynamism positively moderates the dynamic capabilities – novelty-centered BMD relationship, while negatively moderating the dynamic capabilities – efficiency-centered BMD relationship. Moreover, the indirect effects of BSAL on novelty-centered and efficiency-centered BMD via dynamic capabilities are also moderated by environmental dynamism in an opposite manner. Theoretical and practical implications are discussed. Highlights: A balancing strategy of ambidextrous learning (BSAL) is crucial to business model design(BMD). Dynamic capabilities mediate the BSAL–BMD relationship. Environmental dynamism impacts novelty centered and efficiency centered business model design in an opposite manner.